Do Informal Sector Businesses Support Women’s Livelihood? A Case of Butwal Sub-metropolitan of Nepal - Devkota, Jeevanath; Devkota, Devaka (Economic Journal of Nepal, 2019)
Informal sector business seems rapidly increasing in Nepal. This paperexamines the effect of informal businesses on women’s livelihood, which isgenerally not documented in the literature. This study uses primary datacollected from the Butwal sub-metropolitan, Rupandehi District, Province5 of Nepal. Sample size is 300 women entrepreneurs. There is a positivecorrelation between income level and married as well as migrated womenentrepreneurs. Better educated women entrepreneurs are more likely toearn from their businesses in comparison to the less educated women.Women are learning business skills through businesses. Most important,old aged women (around/over 60 years) should not depend on their sonor daughter for their livelihood and for pocket money after starting suchbusinesses.